“I rewrote their story and you can, too”: Black girls’ artistic freedom dreams to create new worlds - Kaler-Jones, Cierra (Frontiers in Education, 2022)
For Black girls, whose histories are often taught in schools through deficit-based narratives, the need to create and reauthor their personal and communal stories is a resistant act that gives their stories permanence in the present and the future. This article explores how Black girls leveraged creative expression to freedom dream in a virtual summer arts program. Theoretically grounded in Abolitionist Teaching and Critical Race Feminism, this study explored eight adolescent Black girls’ (co-researchers) experiences in Black Girls S.O.A.R. (scholarship, organizing, arts, resistance), a program aimed to co-create a healing-centered space to engage artistic explorations of history, storytelling, Afrofuturism, and social justice with Black girls. The study utilizes performance ethnography to contend with the following research question: 1) How, if at all, do adolescent Black girls use arts-based practices (e.g. visual art, music, hair, animation) to freedom dream? Analyses of the data revealed that co-researchers used arts-based practices to reclaim personal and historical narratives, dream new worlds, and use art as activism. In this, co-researchers created futures worthy of Black girl brilliance — futures where joy, creativity, equity, and love were at the center. I conclude with implications for how educators and researchers can employ creative, participatory, and arts-based practices and methodologies in encouraging and honoring Black girls’ storytelling and dream-making practices.